Investigating culture : an experiential introduction to anthropology - Delaney, Carol Lowery , 1940-; Kaspin, Deborah D. , 1953- (Wiley-Blackwell, 2011)
"In its new Second Edition, the innovative and ever-popular Investigating Culture has been updated and revised to incorporate new teacher and student feedback. Carol Delaney and Deborah Kaspin provide an expanded introduction to cultural anthropology that is even more accessible to students. Revised and enhanced new edition that incorporates additional material and classroom feedback Accessible to a wider range of students and educational settings Provides a refreshing alternative to traditional textbooks by challenging students to think in new ways and to apply ideas of culture to their own lives Focuses on the ways that humans orient themselves, e.g., in space and time, according to language, food, the body, and the symbols provided by public myth and ritual Includes chapters that frame the central issues and provide examples from a range of cultures, with selected readings, additional suggested readings, and student exercises"